FORECASTING THE PERLOCUTIVE EFFECT OF POLITICAL SPEECHES BASED ON PHONOSEMANTICS USING THE VAAL SYSTEM - V. Boldyreva (Гуманитарные и юридические исследования)
This study offers a view on a comprehensive pho-nosemantic analysis of modal units, which was performed using the VAAL 2000 system as well as the Praat application (Version 6.0.33), functioning in political speeches. The analysis is carried out from beyond the context and within the context, while the most perlocu-tionally loaded units are the modal verbs must, can and may due to their phonosemantic component, which is defined as a grade scale for the level of effect and the frequency of their use within the framework of speeches delivered by each of the political figures. The analysis suggests that, in the framework of their public speeches, political figures can intentionally use certain modal constructions employed in order to increase their influence on the audience. This is required to convey the speaker's intention to the recipients in the most efficient way, having an impact on their perception of the subjective axiological component of the delivered information. The semantics of modal units can be modified by incrementing additional, hidden semes, the analysis and detection of which helps identify the level of influence and intent of the utterance producer. Politicians' speech usually abounds in functionally loaded modal operators, which is explained by unique phonosemantic potencies. Using them in speeches of such political figures like V. Putin, B. Obama and J. Biden is for a reason. The nuclear and peripheral semantic components of these operators, as well as intonation, and logical stress, help achieve the highest degree of the impact worked on the recipient, while the audience's attention is maintained, and the statement acquires more of information load. It is the presence and functioning of modal operators in the speeches of eminent political figures, associated with the use of a certain intonation, pause and change through the pace of speech, that reveals the use of neurolinguistic programming techniques and, respectively, an attempt to increase the level of impact on the audience.